Pengembangan Modul Pembelajaran Rias Mata Korektif Untuk Siswa XI KKR 1 Di SMKN 7 Tangerang Selatan - Galih Lintang Kinansih; Mari Okatini Armandari; Lilies Jubaedah (Departement of Mathematics Education, 2024)
The development of science and technology (IPTEK) impacts the learning process by providing various sources and learning media, such as textbooks, modules, films, videos, animations, slide shows, and websites. An example of digital literacy implementation in learning is the development of websites as educational media, which falls under the category of e-learning for online learning. This research aims to: (1) produce E-Module learning media for Corrective Eye Makeup material, (2) assess the feasibility of the E-Module, and (3) evaluate the practicality of the E-Module. This study was conducted at SMK Negeri 7 Tangerang Selatan in the Beauty Program, using the Research and Development (R&D) method with the 4D development model (Define, Design, Development, Disseminate). The result of this research is an E-Module in the form of an LMS (Learning Management System) with Corrective Eye Makeup material. The feasibility of the E-Module was evaluated by subject matter experts with a score of 80% and media experts with a score of 81%, both categorized as